Residual levels on medroxyprogesterone acetateimpregnated sponges after estrus synchronization treatment and their relationship with fertility in cyclic goats - Gardón, Juan Carlos; Simonetti, Laura (Brazilian Journal of Veterinary Research and Animal Science, 1997)
A pool polyurethane sponges impregnated with medroxyprogesterone acetate (MAP) was prepared. Real level of progestagen on sponges was checked prior to sponges insertion. 13 cyclic goats were intravaginally treated with MAP-impregnated pessaries for the synchronization of estrus. After 14 days treatment, sponges were removed 48 hours , post-withdrawal goats which exhibited estrus were artificially inseminated. Residual levels of MAP on removed sponges were measured byspectrophotometry at 241 nM. and examined in relation to their fertility. The real dose of MAP was in average 62 mg + 2 mg. High levels (x = 32,46 mg + 9,84 mg) of residual MAP were found on sponges following treatment. The percentage of estrus synchronization was 92,31% and the pregnancy rate was 69,23%. Pregnant goats had significantly higher (p< 0,01) residual amounts of hormone (x = 35,56 mg + 6,06mg) remaining on sponges than non-pregnant goats (x = 20,00 mg ± 10,58 mg).A high positive correlation (r = + 0,7158) was found between residual MAP and fertility. It was concluded that there is a relation between residual level of MAP and the fertility of the synchronized estrus in cyclic goats.